PERAN BAITUL MAL WA TAMWIL (BMT) TAQWA MUHAMMADIYAH DALAM MEMBEBASKAN MASYARAKAT DARI RENTENIR DI KOTA PADANG - Rozalinda Rozalinda (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This research was intended to know any factors that influence people using usurer and how did the BMT Taqwa Muhammadiyah helped people free from usurer in Padang. This research applying descriptive qualitative technique. The finding of this research showed that people were still using usurer in overcoming their financial problems due to (1) emergency need on business assistances, (2) quick process, simple procedure and shortherm paybak periode, (3) lack of bank and non bank access (4) they do not have any information of existing BMT, (5) depleted concern on religious believe on leaving excessive interest. Moreover the finding also found that BMT Taqwa Muhammadiyah had not yet provided significant financial assistance toward vendors.